Vydūnas and Indian Philosophy - Šaulauskas, Marius Povilas (Problemos, 1988)
In the paper an attempt is made to establish conceptual and compositional similarity between the philosophy of the Lithuanian thinker Vydūnas and traditional Indian philosophy which is conceived as an architectonical whole, i.e., able to invoke definite methodological attitudes. The classical Buddhist exemplification of “four noble truths” is claimed to be the basis of the architectonical structure. Such a structure is revealed in the general formulation of Vydūnas’ methodological attitude.